Eksplorasi Nilai Altruisme dan Praktik Filantropi Islam di Masa Pandemi Covid-19: Exploration of Altruism and the Practice of Islamic Philanthropy During the Pandemic - zakiyatul fuadah (Direktorat Jenderal Bimbingan Masyarakat Islam, 2021)
Abstraction At the beginning of 2020 the world was shocked by the pandemic called Covid-19. Its massive spread causes paralysis in various sectors of life such as the economy, education, social and religion. Indonesia is also affected by this impact; various policies have been issued by the government to overcome this impact. One of them is the policy of limiting community activities called social distancing that affects the decrease in economic activity, even some large companies must terminate their employees. This condition stimulated the Islamic philanthropic movement. This study will explore the community altruism and the practice of Islamic philanthropy as an embodiment of social solidarity in Indonesia during a pandemic. This research is field research with a qualitative descriptive approach by collecting data through documentation and interviews with the people involved. A literature study was also carried out by collecting data from various literatures from the books, laws and regulations, journals, and news related. The results of the study show that the altruism of the Indonesian people is still well preserved and explored through the existence of several philanthropic programs and practices. This program is, at least, able to answer the problems of the community caused by the pandemic, as well as support government programs that are short-term and temporal. Furthermore, its existence is also able to increase public awareness and solidarity to keep sharing during a pandemic.